2018
DOI: 10.1177/1358863x18763096
|View full text |Cite
|
Sign up to set email alerts
|

The role of novel cytokines in inflammation: Defining peripheral artery disease among patients with coronary artery disease

Abstract: Coronary artery disease (CAD) patients with concomitant peripheral artery disease (PAD) experience more extensive and calcified atherosclerosis, greater lesion progression and more common coronary events compared to patients with CAD only. To characterize the distinct features of this aggressive atherosclerotic disease, we studied novel cytokines that code different stages of atherogenesis. One hundred and eighty consecutive subjects (60 patients into each group of CAD+PAD, CAD and controls) were recruited amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 32 publications
(44 reference statements)
0
11
0
Order By: Relevance
“…Cardiovascular diseases (CVDs), especially coronary artery disease (CAD), continue to be the major causes of deaths worldwide. CAD is caused by coronary atherosclerosis, an inflammatory disease resulting from the formation of plaques and subsequent obstruction of coronary arteries . Despite recent advances in the diagnosis, treatment and prognosis of cardiovascular diseases, there is still a clinical need to identify novel diagnostic and prognostic biomarkers that pave the way for new therapeutic interventions.…”
Section: Introductionmentioning
confidence: 99%
“…Cardiovascular diseases (CVDs), especially coronary artery disease (CAD), continue to be the major causes of deaths worldwide. CAD is caused by coronary atherosclerosis, an inflammatory disease resulting from the formation of plaques and subsequent obstruction of coronary arteries . Despite recent advances in the diagnosis, treatment and prognosis of cardiovascular diseases, there is still a clinical need to identify novel diagnostic and prognostic biomarkers that pave the way for new therapeutic interventions.…”
Section: Introductionmentioning
confidence: 99%
“…Recent evidence proposes a critical role of inflammatory processes in the pathophysiology of PAD [12-15]. Platelets employ pattern recognition receptors toll-like receptor 4 (TLR4) and nucleotide-binding domain leucine rich repeat containing protein 3 (NLRP3) [16-19].…”
Section: Introductionmentioning
confidence: 99%
“…found that the N‐terminal domain of Nogo‐A inhibits cell adhesion and axonal outgrowth through several integrins, including α v β 3 (Hu and Strittmatter, ). ER‐resident Nogo‐B protein can not only localize to the plasma membrane but also secrete into extracellular space (Acevedo et al ., ; Ozkaramanli Gur et al ., ). Nogo‐B in HCC cells exhibited a consistent distribution in our work, that it can be detected both on HCC cell surface and in the cell culture medium (data not shown).…”
Section: Discussionmentioning
confidence: 97%